Conceptual spaces and consciousness: Integrating cognitive and affective processes - Pereira Jr., Alfredo [UNESP]; Almada, Leonardo Ferreira [UNESP] (World Scientific Publishing, 2011)
In the book Conceptual Spaces: the Geometry of Thought [2000] Peter Gärdenfors proposes a new framework for cognitive science. Complementary to symbolic and subsymbolic [connectionist] descriptions, conceptual spaces are semantic structures constructed from empirical data representing the universe of mental states. We argue that Gärdenfors' modeling can be used in consciousness research to describe the phenomenal conscious world, its elements and their intrinsic relations. The conceptual space approach affords the construction of a universal state space of human consciousness, where all possible kinds of human conscious states could be mapped. Starting from this approach, we discuss the inclusion of feelings and emotions in conceptual spaces, and their relation to perceptual and cognitive states. Current debate on integration of affect/emotion and perception/cognition allows three possible descriptive alternatives: emotion resulting from basic cognition; cognition resulting from basic emotion, and both as relatively independent functions integrated by brain mechanisms. Finding a solution for this issue is an important step in any attempt of successful modeling of natural or artificial consciousness. After making a brief review of proposals in this area, we summarize the essentials of a new model of consciousness based on neuro-astroglial interactions. © 2011 World Scientific Publishing Company.
Keywords: conceptual spaces; Consciousness; correlations; homeomorphism; methodology; Conceptual spaces; Cognitive systems; Gallium; Semantics; Behavioral research